Attitude Towards Scientific Livestock Technologies : A Multi-Stakeholder Analysis In Uttar Pradesh, India - Rathod , Prakashkumar; Chander, Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
An ex-post-facto exploratory study was conducted to assess the attitude of multi-stakeholders towards livestock technologies developed by scientists in Uttar Pradesh state of India. The study reveals that attitude of scientists and Extension experts were more favorable towards the livestock technologies while the attitude of farmers was less favourable towards the livestock technologies developed by the scientists. The study also indicated that attitude of farmers towards livestock technologies was found to be significantly correlated with education and decision making ability of the farmers. The study concluded that, there is a need to generate and disseminate technologies based on the demands of livestock farmers for an effective diffusion and adoption of technologies leading to improved quality and productivity in livestock sector.